Spiritual Intelligence: a Structural Perspective - Jucevičienė, Palmira; Škėrienė, Sandrita (Pedagogika, 2016)
This paper aims to bring more clarity into the structure of spiritual intelligence. This construct integrates the meanings of both spirituality and intelligence. The definitions of intelligence have strong emphasis on capacities and higher level abilities (such as abstract reasoning, problem solving and decision making). Many definitions of spirituality represent it as a holistic, multidimensional human phenomenon that transcends the physical, social, and psychological being. Spirituality, as seen from the perspective of intelligence, has to be understood as distinct from religiousness. Various authors provide different definitions of spiritual intelligence. The analysis of literature sources has shown that the concept of spirituality is very broad, but it has to be narrowed down when integrated with the concept of intelligence into the construct of spiritual intelligence because the spirituality becomes a feature of the intelligence as an ability. It means that spirituality should both retain its own essence and to meet the criteria of intelligence. Therefore, the following structure of spiritual intelligence, offered by D. B. King (2008) emerges as the most appropriate: critical existential thinking, personal meaning production, transcendental awareness, and conscious state expansion.